Comparative analysis of China's Health Code, Australia's COVIDSafe and New Zealand's COVID Tracer Surveillance Apps: a new corona of public health governmentality?. (February 2021) - Yang, Fan; Heemsbergen, Luke; Fordyce, Robbie
The onset of the COVID-19 pandemic and the subsequent lockdown of cities worldwide generated a dramatic increase in the use of public health trac(k)ing technologies. This article presents an empirical analysis of China's Health Code on WeChat and Alipay, Australia's COVIDSafe and New Zealand's COVID Tracer. We ask: how does app-based public health monitoring differ from prior forms of state tracking and corporate surveillance, and interface with public and private ideals of health and citizenship? Based on a comparative analysis of the selected apps and the political economy that surrounds their code and implementation, we argue that there is a new corona of surveillance to address COVID-19 crises by intensifying the diffusion of national surveillance technologies and framing these into justifiable moral practice. In conclusion, we identify a new 'corona' of public health governmentality during COVID-19 pandemic through an intensification of top-down institutional data extraction from human bodies.